Smoke Screen : Estimating the Tax Pass-Through to Cigarette Prices in Pakistan - Cevik, Serhan (IMF Working Papers; Working Paper, 2016)
This paper estimates the magnitude and speed of tax pass-through across tobacco products at different price points in Pakistan by using a novel dataset of monthly observations on cigarette prices in 50 cities during the period 2004-2015. The pass-through of cigarette taxes to retail prices is found to occur within two months, but is mostly incomplete in magnitude. On average, a one-rupee tax increase is estimated to lead to an increase of only PRs 0.8 in retail cigarette prices. This is driven by the fact that tobacco manufacturers absorb a significant part of the tax increase. For the premium brand, however, I observe full passthrough, indicating possibilities of different demand elasticities across product tiers. These findings are likely to be attributable to competitive market pressures, especially at the budget end of the price spectrum, possibly stemming from changing consumption patterns with greater awareness of health risks as well as the impact of illicit domestic production.